La lutte contre la cybercriminalité au regard de l’action des États - Boos, Romain (Université de Lorraine, 2016)
Le XXIe siècle voit la consécration des technologies numériques comme la fin du Moyen Âge a vu celle de l’imprimerie. L’ère numérique ignore désormais toutes les frontières. Elle permet l’accès à la culture et à la connaissance, favorise les échanges entre les personnes. Elle rend possible la constitution d’une économie en ligne et rapproche le citoyen de son administration. Les technologies numériques sont porteuses d’innovation et de croissance, en même temps qu’elles peuvent aider ou accélérer le développement des pays émergents. Mais un certain pessimisme vient tempérer cette approche idéaliste. Tous les progrès génèrent aussi de nouvelles fragilités et vulnérabilités propices aux menaces ou aux risques, car ils aiguisent l’imagination des criminels. La cybercriminalité est désormais une réalité. Elle est d’autant plus dangereuse qu’elle pénètre au sein des familles, là où la délinquance ordinaire n’avait pas accès jusqu’à présent. Dès lors, cette nouvelle forme de criminalité laisse apparaître comme une évidence, l'adaptation du système judiciaire. En effet, face à ces atteintes, il existe bel et bien des lois qui sont d'ores et déjà appliquées à l’Internet. Mais sont-elles réellement efficaces ? Dans le même sens, la coopération interétatique est-elle également suffisante pour lutter efficacement contre la cybercriminalité ? Ainsi, il importe de se demander si dans notre société moderne, le cadre normatif et la coopération institutionnelle tant européenne qu'internationale, sont suffisants et efficaces pour sanctionner les infractions cybercriminelles ? The twenty-first century sees the consecration of digital technologies just as the end of the Middle-Ages saw the creation of printing. Henceforth, the digital era has no limits. It gives access to culture and knowledge, encourages the exchanges between people. It allows the constitution of an economy online and brings citizens closer to their adminitration. Digital technologies generate innovation and growth, and can help or accelerate the development of the emergent countries as well. But a certain pessimism moderates this idealistic approach. All these advances also generate new fragilities and vulnerabilities propicious to threats or risks, as they stimulate the criminals' imagination. Now, cybercriminality has become reality. It is all the more dangerous as it penetrates within families, where ordinary delinquency didn't exist until now. From now on, this new kind of criminality made it obvious that the judicial system had to be adapted. Indeed, faced with these violations, there are of course laws that are applied here and now to the Internet. But, are they really efficient? In the same way, is the intersate cooperation also sufficient to fight against cybercriminality? So, it is important to wonder whether, in our modern society, the legislative framework and the institutional cooperation, both european and international, are sufficient and efficient to penalize the cybercriminal offences.
Keywords: Anonymat; Anonymity; Cheval de Troie; Computer sabotage; Cybercriminality; Cybercriminalité; Cyberespace; Cyberterrorisme; Droit; Informatique; Internet; Sabotage informatique; Trojan Horse; Virus informatiques; Web

The United Nations Convention on the Use of Electronic Communications in International Contracts at Ten: Practical Relevance and Lessons Learned - Castellani, Luca G. (Journal of Law, Society and Development, 2016)
The United Nations Commission on International Trade Law prepared the first global treaty specifically devoted to electronic commerce law, the United Nations Convention on the Use of Electronic Communications in International Contracts. That treaty builds on the highly successful UNCITRAL Model Law on Electronic Commerce and the UNCITRAL Model Law on Electronic Signatures. This article describes the main goals of the Electronic Communications Convention and its scope of application. In particular, it illustrates how that Convention may fully enable the use of electronic means under other widely adopted treaties such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards and the United Nations Convention on Contracts for the International Sale of Goods. The article also describes the main substantive provisions of the Electronic Communications Convention, in particular clarifying how that Convention updates and completes the provisions of the UNCITRAL Model Law on Electronic Commerce. This Model Law is the backbone of electronic commerce law in numerous countries and a de facto legislative standard insouthern Africa. Finally, the article describes the manner (or patterns) in which the adoption of the Electronic Communications Convention takes place. It stresses that, while the Convention is often used as a source of inspiration for domestic law reform, in order for it to achieve all its intended goals, its formal adoption as a treaty is necessary. The final message is therefore a call upon all states to consider the adoption of that Convention in order to support the broader use of electronic means, especially in the light of the implications for economic development and the promotion of paperless trade.
Keywords: Convention adoption patterns; Digital signatures; Electronic communications; Electronic contracting; Legal harmonisation

Convention de l’Union africaine sur la cybersécurité : plaidoyer pour un dépassement des traditions - Kablan, Serge; Oulai, Arthur; Sanni Yaya, Mouhamadou (Revue de droit des affaires internationales, 2016)
« Au commencement était l’Afrique ». Cette évocation, que continuent d’étayer les découvertes successives de fossiles d’Australopithèques, est à la Commission de l’Union africaine l’indication des origines temporelle et géographique de « l’immense aventure humaine du progrès ». Le continent, tout autant exposé aux phases contemporaines de l’équipée, entendues particulièrement des développements technologiques, a engagé plusieurs initiatives d’accompagnement dont l’une des plus récentes, promue par l’Union africaine, vise à doter ses 54 États membres d’une convention instituant un cadre juridique de confiance pour la cybersécurité. Il y a, dans cette convention, l’ambition triple d’organiser les transactions électroniques, d’assurer la protection des données à caractère personnel et de lutter contre la cybercriminalité. D’un point de vue prospectif, les auteurs apprécient l’effectivité de la convention eu égard à la question spécifique du commerce électronique, en tentant de déterminer si, dans sa forme comme dans sa substance, cet instrument a les moyens de satisfaire aux préoccupations de sécurité juridique et technique des différents milieux concernés.

Elektronik ortamda gerçekleşen alım satım işlemlerinin İslam Hukuku açısından değerlendirilmesi (İslam Hukuku açısından e-ticaret) - Bayraktar, Ahmet (Ankara Üniversitesi, 2016)
Araştırmamız bugüne kadar ülkemizde İslam hukukçularınca doktora düzeyinde girilmemiş ve değerlendirilmemiş bir mesele olan İslam hukuku açısından elektronik ticareti konu edinmiştir. Bu manada ilk bölümde İslam hukuku açısından ticaret hukuku kavramlarına kısa bir değini yapılmış ve bununla ilgili çok temel bilgiler verilmiştir. İkinci bölümde İslam hukuku açısından e-ticaret incelenmiş, E-ticaretin İslam hukuk kavramlarıyla nasıl anlaşılabileceğine ve anlatılabileceğine dair görüş ve tespitlerimiz sunulmuştur. Elektronik ortamda akitleşme, irade beyanı gibi yeni durumların analizi yapılmıştır. Üçüncü bölümde ise fıkhî hükümleri açısından e-ticaret incelenmiştir. Bu bölümde de e-ticarette yeni ortaya çıkan durumlar, kavramlar ve olgular incelenmiştir. Fıkhî açıdan hangi kavramlarla açıklanacağı hususunda kanaatlerimiz sunulmuştur. İkinci bölüm değerlendirme ve analiz ağırlıklı iken üçüncü bölümde daha çok pratik sonuçları açısından durum incelenmiş, bu hususta literatüre girmesi gerektiğini düşündüğümüz yeni kavramlar ve tasnifler de zikredilmiştir. Son olarak da mevcut modern yasalarda e-ticaretin nasıl ele alındığı gösterilmiş, İslam hukuku açısından nasıl değerlendirilebileceğine dair görüşlerimiz arz edilmiştir. This work is about electronic commerce in İslamic law which has not been studied or evaluated by anyone with such a scale until now. In this sense, at the first section, the concepts of commerce law have been mentioned briefly by the view of Islamic law, and has been given basic knowledge. At the second section, E-commerce regarding to concepts of Islamic law has been examined. Our opinions and detections about it like how this is must be understood with the notions of Islamic law have been presented. The conceptual analysis of new situations such as contracting, declaration of intention, on the İnternet has been done. At the last section, e-commerce regarding rules of Islamic law has been examined. In this section, new situations and concepts that just emerged have been examined. Our opinions have been presented. As the second section weighted with assessment and analysis, at the third section, the case has been examined rather practically. New concepts and categorizations that must be added to the literature have been mentioned.
Keywords: E-commerce; Electronic commerce; Elektronik ticaret; Islamic Law; İslam Hukuku